Antidiabetic Evaluation of Isolated Compounds from Medicinal Plants Coccinia Grandis and Tinospora Cordifolia in Alloxan Induced Diabetic Rat Model - Ram Bindurani L G P; Singh Anoop (International Journal of Pharma and Bio Sciences, 2020)
The World Health Organization (WHO) estimates that about 80% of the population living in the developing countries relies almost exclusively on traditional medicine for their primary health care needs. In almost all the traditional medicine, the medicinal plant plays a major role and constitutes the backbone of traditional medicine Tinospora cordifolia commonly named as “Guduchi” is known for its immense application in the treatment of various diseases in the traditional Ayurvedic literature2. Coccinia grandis is used by humans mostly as a food crop in several countries in Australia, Asia, Caribbean, and the southern United States, Pacific Islands and commonly named as “Ivy gourd or scarlet gourd”. The present study was aimed to evaluate the anti-diabetic activity of isolated compounds from aerial parts of Tinospora cordifolia (Guduchi) and Coccinia grandis in alloxan induced diabetic rats. Diabetic wistar albino rats were treated with standard drug glibenclamide and prepared drug formulation in two different doses 250 mg and 500 mg/kg. Acute toxicity studies conducted revealed that the administration of graded doses of both the crude aqueous and ethanol extracts (up to a dose of 4000 mg/kg) of both plant did not produce significant changes in behaviors such as alertness, motor activity, No death was observed up to the dose of 4 g/kg body weight. The mice were physically active. These effects were observed during the experimental period (72 hrs). The result showed that in single dose; the plant extracts had no adverse effect, indicating that the medium average lethal dose (LD50) could be greater than 4 g/kg body weight in mice. Based on these results 1/10th of the maximum safe dose was taken for further pharmacological screening. Hypoglycemic effect was evaluated in these rats and the efficacy of isolated compounds was administered in alloxan induced diabetic rats. At the end of the study, blood glucose levels statistically analyzed based on the results. Isolated compounds (A,B,C,D named taxaterone, tinsoporin, teraxerol and beta sitosterol respectively) produced a significant reduction in blood glucose level when compared with non-treated diabetic rats. So the present research work confirmed that the isolated compounds possess hypoglycemic effects significantly.